Casing layer and effect of primordia induction in the production of Agaricus subrufescens mushroom - Martos, Emerson Tokuda; Zied, Diego Cunha [UNESP]; Junqueira, Pedro Paulo Gadoni; Rinker, Danny Lee; Da Silva, Romildo; Toledo, Rômulo César Clemente; Dias, Eustáquio Souza (Kasetsart University Research and Development Institute, 2017)
Agaricus subrufescens growers have faced difficulties in standardizing and maintaining optimal production yield, even when they produce or acquire quality substrate, as cultivation success is also related to the quality of the casing layer and the production environment. The production of A. subrufescens was evaluated using different casing layers and methods for primordia induction. Three experiments were carried out: 1) to evaluate the effect of dolomitic limestone in the casing layer; 2) to evaluate the effect of different combinations of mineral and organic materials used as the casing layer; and 3) to evaluate the effect of temperature in primordia induction with two commercial strains. The results demonstrated that an increase in the limestone concentration in the casing resulted in a superior yield (16.7%). Casing layer combinations using organic substrate + sand (proportion 1:1, volume to volume) resulted in a greater yield (19.2%). Temperature did not affect primordia induction.
Keywords: Agaricus subrufescens; Sun mushroom; Technology of production; Yield